The Mediating Processes between Depression and Cardiac Adverse Events - R Bagherian (Babol University of Medical Sciences, 2011)
Depressive symptoms are common among post myocardial infarction (MI) patients and may cause negative impacts on cardiac prognosis. The studies supported that depression is an independent risk factor for poor prognosis in post MI patients. The various articles about the plausible mechanisms between post-MI depression and adverse outcomes were found and studied. The plausible pathways involved in this link were described.The study of the results of these articles showed that the different behavioral, neuroendocrinological, and immunological, arrhythmias mechanisms and increased thrombosis are likely the pathways by which depression may cause increased risk for adverse outcomes and mortality. It seems that particularly increased thrombosis and arrhythmias may cause increased risk for mortality in depressed patients with heart disease. This review showed important role of psychological and biological pathways for increasing risk of mortality and adverse consequences among patients with post MI depression.